Potato response to silicone compounds (micro and nanoparticles) and potassium as affected by salinity stress - Kafi, Mohammad; Nabati, Jafar; Saadatian, Bijan; Oskoueian, Armin; Shabahang, Javad (Italian Journal of Agronomy, 2019)
Salinity of irrigation water is an important limitation factor in crop production such as potato worldwide. Foliar application of anti-stress compounds containing mineral nutrients is one of the possible solutions for salinity mitigation. In this field experiment the effects of silicone compounds on potato (cv. Agria) performance was studied as a split plot based on randomised complete block design with three replications at Ferdowsi University of Mashhad, Iran, during 2016 cropping season. Treatments included irrigation salinity [0.3 (non-stress), 5, 8 and 12 dS.m–1] and foliar application of potassium sulphate (1000 ppm), sodium silicate nanoparticles (400 ppm) and silica (1000 ppm). Results indicated that salinity decreased transpiration rate, stomatal conductance, quantum yield of PSΙΙ, membrane stability index, carotenoids, tuber number per plant and tuber yield while it improved water use efficiency and tuber dry matter percentage. Foliar application of anti-stress compounds positively affected quantum yield of PSΙΙ, carotenoids content, DPPH radical scavenging activity, tuber number per plant, tuber yield and tuber dry matter percentage. Although, application of all compounds improved most biochemical and photosynthetic traits, but ameliorative effect of the two silicon compounds, especially sodium silicate nanoparticles was more evident. It seems that silicon application could be an effective strategy in reducing salinity effects and its efficiency will be increased when is used as nanoparticles.